Cognitive accounts of second language acquisition: critical period and age effects - Figueiredo, Sandra (2018)
According to previous framework, the main hypothesis is that language could be acquired with accuracy just in a critical period, until puberty. The critical period effects are present both in first and second language acquisition situations. However the mastery and native-like competence believed as a classic achievement by the youngest learners (infants), could be compromised for several other maturational constraints which are not favourable. In the scope of PhD research, is been developed a battery, in electronic format, to observe differences, at phonological processing and other cognitive levels in the second-language field, between children, adolescents and adults. According to theories and findings in the neuroplasticity area, it was objective to analyse the metalinguistic competence and cognitive processes involved in it, considering age, gender and also nationality and mother tongues of the individual. Here will be presented and discussed implications of some results regarding performance in the dichotic hearing test.